Design of a 120V, 5A SEPIC DC-DC Converter for Unipolar 120V DC Microgrid - Abdulkareem Mokif Obais; Ali Abdulkareem Mukheef (Universitas Negeri Surabaya or The State University of Surabaya, 2025)
SEPIC is a DC-DC converter that operates in both boost and buck modes, thereby reducing voltage stress on the active power switches. It is utilized in electric vehicles, marine vessels, and aircraft to minimize dimensions, mass, maintenance, and operational expenses while enhancing efficiency, safety, and dependability. DC microgrids, characterized by their straightforward topology and economical materials, provide enhanced efficiency relative to AC microgrids. This work reviews the previous literature concerning SEPIC converters and DC-DC microgrid applications. This paper presents a SEPIC based DC-DC converter designed for direct connection to a unipolar 120V DC microgrid and capable of delivering 600W of DC power. It is outfitted with a current sensor and a protective switch to provide self-protection against microgrid disturbances, such as brief short circuits. The converter has been designed and evaluated using PSpice. The simulation results indicated that during a sudden disturbance in the DC microgrid, the current sensor detected an excessive current, prompting the control circuit to deactivate the protective switch. This action isolated the input voltage from the converter circuit, leading to an immediate reduction of the input current to zero and a subsequent decline of the output voltage toward zero. The condition endured for approximately 50 milliseconds, anticipating a possible recovery from the disruption. Therefore, the simulation results confirmed the design methods of the proposed converter and demonstrated adequate protection against highcurrent events.